Flowering of Woody Bamboo in Tissue Culture Systems - Yuan, Jin-Ling; Yue, Jin-Jun; Gu, Xiao-Ping; Lin, Choun-Sea (Frontiers in Plant Science, 2017)
Flowering and subsequent seed set are not only normal activities in the life of most plants, but constitute the very reason for their existence. Woody bamboos can take a long time to flower, even over 100 years. This makes it difficult to breed bamboo, since flowering time cannot be predicted and passing through each generation takes too long. Another unique characteristic of woody bamboo is that a bamboo stand will often flower synchronously, both disrupting the supply chain within the bamboo industry and affecting local ecology. Therefore, an understanding of the mechanism that initiates bamboo flowering is important not only for biology research, but also for the bamboo industry. Induction of flowering in vitro is an effective way to both shorten the flowering period and control the flowering time, and has been shown for several species of bamboo. The use of controlled tissue culture systems allows investigation into the mechanism of bamboo flowering and facilitates selective breeding. Here, after a brief introduction of flowering in bamboo, we review the research on in vitro flowering of bamboo, including our current understanding of the effects of plant growth regulators and medium components on flower induction and how in vitro bamboo flowers can be used in research.